Peru’s Works for Taxes Scheme : An Innovative Solution to Accelerate Private Provision of Infrastructure Investment - Del Carpio Ponce, Paola Elvira (International Finance Corporation, Washington, DC, 2018)
Created in Peru in 2008, Works for Taxes is an innovative approach to accelerating infrastructureinvestment. It allows private firms to “pay” their income taxes in advance through the execution ofpublic works projects. By accepting infrastructure projects in lieu of future taxes, national, regional, and local governments can forego mobilization of public funds and reduce the burden on government budgets, as the private sector assumes the upfront costs and management of new infrastructure projects. The mechanism’s success derives from its ability to align public and private sector incentives for better quality projects and more efficient use of funds. Works for Taxes has great potential for replication in other emerging market countries with similar obstacles to infrastructure investment.